Evaluasi Kinerja KSP Satria B Cilongok Menggunakan Kriteria Malcolm Baldrige - Laily, Atiya Zulkhatul; Shafrani , Yoiz Shofwa; Insyani, Intan Ayu; Abidin, Nurlita Azizah (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to evaluate the performance of KSP Satria B Cilongok using the Malcolm Baldrige Framework for Performance Excellence. The research employed a qualitative descriptive approach with data collected through direct observation and in-depth interviews with the cooperative’s leadership on May 4, 2025. Analysis was conducted based on seven categories within the Malcolm Baldrige Excellence Framework. Findings indicate that KSP Satria B Cilongok has implemented visionary leadership, customer-focused service, data-driven management, and effective risk and workforce management. The cooperative’s performance continues to improve, demonstrated by stable growth in members, net income (SHU), and transaction volume. Furthermore, adherence to organizational ethics and transparency has been a key factor in building member trust. This study contributes by integrating the Malcolm Baldrige principles into the management of small to medium-sized savings and loan cooperatives in Indonesia, presenting a novel application of the framework in the local context